Comparison of a novel handheld accelerometer-based navigation system and conventional instrument for performing distal femoral resection in total knee arthroplasty: a randomized controlled trial - Xu, Xingquan (Ann Transl Med, 2019)
BACKGROUND: This prospective study aimed to compare the efficacy of a novel, hand-held, accelerometer-based navigation system (i-JOIN knee navigation system) for distal femoral resection in total knee arthroplasty (TKA) with conventional instrument. METHODS: A multi-center, double-blinded, randomized controlled trial (RCT) was conducted. A total of 79 consecutive patients scheduled for primary TKA were enrolled and divided into navigation group (39 patients) and conventional group (40 patients). Post-operative mechanical and component position were evaluated through full-leg weight bearing X-ray. Pre-operatively and 1 week post-operatively, adverse events were recorded. Intraoperative surgical time and blood loss were also recorded. RESULTS: The mean outlier of 180° neutral mechanical axis was 1.60° (SD 1.11°) in navigation group and 2.30° (SD 2.06°) in conventional group (P=0.0917). Thirty-eight patients (97.4%) in navigation group and 35 patients (87.5%) in conventional group had an alignment which was ≤3°away from the neutral mechanical axis (P=0.2007). α angle between the navigation group and conventional group was not statistically different (89.81° vs. 89.76°, P>0.05), as well as adverse events rate post-operatively. The operative time of navigation group was significantly longer than that of control group (114.54±35.34 vs. 100.33±28.38 min, P=0.0493), whereas the intraoperative blood loss was not significantly different. CONCLUSIONS: i-JOIN knee navigation system had equivalent results for distal femoral resection in TKA compared with the conventional technique.